As jóias de Mallarmé e Barthes (ModaPalavra e-periódico, 2009)
This study , approach - if the figure of StÈphane MallarmÈ what , the end of day nineteenth century the author stÈphane MallarmÈ created and composed alone a magazine of fashion; La DerniËre Mode ñ gazette du monde et de la famille. It was various turns evoked by Roland Barthes in interview and too in the last your text Des joyaux aux bijoux" (1961). this approximation between literature and fashion happened in other works of Barthes like: History and sociology of the clothing (1957), Language and clothing (1959), In this year the blue thing is in fashion (1960), Dandyism and Fashion (1962), Fashion and to human studies (1966), The duel chanel-CourrÈges (1967) and the System of the fashion, book 1967. The approximation of the texts of MallarmÈ and Barthes potencial concepts of the correspondence between literature and fashion. Barthes reader of Balzac, Saussurre and Trubetskoi, becomes an arqueology of seasonal magazines of fashion, and it is this way of aesthetic expression, that it links and MallarmÈ remade and turned the daily life of the Parisian women into sign.
Keywords: fashion; literature; magazine; Mallarmë; Barthes